Tradition in a mirror of present and future - Shyrap, Regina O. (The New Research of Tuva, 2010)
Work of the laureate of the 3 degree of the essay contest "Tuva-2050: vision of the future".
Keywords: konkurs; Tuva-2050; foresight; youth; essay